MEMBANGKITKAN UMKM DI TENGAH PANDEMI COVID 19 - Nasution, Winda Suci Lestari (Universitas Esa Unggul, 2021)
Micro, Small and Medium Enterprises (MSMEs) are one of the business units that play an important role in economic growth and development in Indonesia. MSMEs are also one of the supporters of the economy in Indonesia, especially for the lower and middle class people. MSMEs have a strategic role in the government's efforts to overcome poverty and unemployment, because MSMEs can absorb labor so that unemployment due to not absorbing the labor force in the world of work is reduced. The Covid-19 pandemic that has hit the whole world, globally, including Indonesia, of course has an impact on various sectors, especially in the economic sector. The call to prevent the chain of spreading this virus requires people to stay at home and reduce activities outside the home. All aspects of life are affected and forced to change the pattern of life, work patterns, thinking patterns and other patterns that humans run. The negative impact of the COVID-19 pandemic has hampered the growth of MSMEs. Indonesia, which is dominated by MSMEs as the backbone of the national economy, is affected by the COVID-19 pandemic, not only in terms of production and income but also in the number of workers that must be reduced and others. MSMEs lack resilience and flexibility in dealing with the COVID-19 pandemic due to several things, such as the low level of digitalization, difficulties in accessing technology and a lack of understanding of strategies to survive in business. Kata kunci : MSMEs, economy, covid 19